PENGARUH APLIKASI BIONEMATISIDA PURPUREOCILLIUM LILACINUM TERHADAP KOMUNITAS NEMATODA PADA LAHAN JAMBU KRISTAL - Dewi, Ni Kadek Emi Sintha; Zahra, Fatimah Az; Swibawa, I Gede; Suharjo, Radix; Fitriana, Yuyun; Maryono, Tri; Lestari, Puji; Helina, Selvi; Aulia, Shifa Veronica; Wardiyani, Wardiyani; Marlinawati, Fransiska Dina; Basuki, Muh.; Ratdiana, Ratdiana (AGRICA, 2025)
Crystal guava (Psidium guajava var. crystal) is a high-value horticultural commodity, but its production in several regions has declined due to infestations by plant-parasitic nematodes. This study aimed to evaluate the effects of a bionematicide formulated with Purpureocillium lilacinum on the composition and diversity of soil nematode communities in crystal guava cultivation. Assessments were conducted on nematode abundance, absolute frequency, prominence value, and diversity metrics, including the Shannon index, evenness, dominance, and species richness, before and after the application of compost and bionematicide treatments. The results revealed the presence of 11 nematode genera, with Aphelenchus being the most dominant. Both compost and bionematicide treatments led to a decline in most genera, except Aphelenchoides, which increased in both abundance and prominence, and Rhabditis, which showed an increase in abundance but a reduction in ecological value. Post-treatment measurements indicated decreases in diversity, evenness, and richness indices, alongside an increase in dominance, particularly following compost application. These findings suggest that while P. Lilacinum is effective in targeting certain nematode groups; however, it may also reduce overall nematode community diversity, potentially leading to the dominance of the Aphelenchus genus. Thus, its application should be accompanied by ecological impact assessments to ensure the long-term sustainability of soil ecosystems.